Genetic Diversity of Yeasts from Fermented Orange Juice Based on PCR-RFLP and Sequence Analysis of the Internal Transcribed Spacer Regions - SUSAN SOKA; ANASTASIA SUSANTO (Microbiology Indonesia, 2010)
Orange is one of the most valuable and common fruits in Indonesia. High glucose level in orange juice provides good growth conditions for yeasts. In this study, yeasts were isolated from fermented orange juice and subjected to diversity analysis. The analysis was conducted using restriction fragment length polymorphism on the internal transcribed spacer (ITS) region (including ITS1, 5.8S rRNA gene and ITS2), which was amplified using PCR with ITS1 and ITS4 primers.Restriction enzymes used in this research were HhaI, HinfI and HaeIII. A total of 24 yeast isolates were obtained from three different kinds of fermented orange juices (Indonesian Medan orange, Sunkist orange and Indonesian Pontianak orange). RFLP analysis of ITS regions revealed different amplified PCR fragment sizes and restriction profiles for each type of orange juice. However, all yeasts isolated from the same type of orange juice showed identical restriction patterns. Sequencing of ITS regions showed that three different yeast species were detected from each type of orange, e.g. Pichia veronae from Indonesian Pontianak orange, Cryptococcus albidosimilis from Sunkist orange and Issatchenkia orientalis from Indonesian Medan orange.